The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fimmu.2017.00659
|View full text |Cite
|
Sign up to set email alerts
|

Neoglycoconjugate of Tetrasaccharide Representing One Repeating Unit of the Streptococcus pneumoniae Type 14 Capsular Polysaccharide Induces the Production of Opsonizing IgG1 Antibodies and Possesses the Highest Protective Activity As Compared to Hexa- and Octasaccharide Conjugates

Abstract: Identifying protective synthetic oligosaccharide (OS) epitopes of Streptococcus pneumoniae capsular polysaccharides (CPs) is an indispensable step in the development of third-generation carbohydrate pneumococcal vaccines. Synthetic tetra-, hexa-, and octasaccharide structurally related to CP of S. pneumoniae type 14 were coupled to bovine serum albumin (BSA), adjuvanted with aluminum hydroxide, and tested for their immunogenicity in mice upon intraperitoneal prime-boost immunizations. Injections of the conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
1
23
0
3
Order By: Relevance
“…The synthetic tetrasaccharide conjugate ST14 ( Fig. 1), resembling the previously identified repeating unit of the widespread S. pneumoniae ST14 serotype (21), was included to show that nonproblematic isolated serotypes can in principle also be substituted by synthetic antigens.…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic tetrasaccharide conjugate ST14 ( Fig. 1), resembling the previously identified repeating unit of the widespread S. pneumoniae ST14 serotype (21), was included to show that nonproblematic isolated serotypes can in principle also be substituted by synthetic antigens.…”
Section: Resultsmentioning
confidence: 99%
“…Effective short, branched epitopes have also been identified for the Pn14 PS: Safari et al demonstrated that one RU of the Pn14 PS (Figure 1c) is essential and sufficient for inducing protective Pn14-specific antibodies: the presence of the trisaccharide branch point in an epitope is crucial for anti-Pn14 antibody recognition and the extra galactose contributes to the immunogenicity of the epitope [14]. Kurbatova et al recently identified a similar branched tetrasaccharide as the most effective epitope for Pn14 PS [15]. In contrast, linear Pn14 PS fragments were found to be completely ineffective: none of a range of short linear epitopes of the PS backbone were recognized by Pn14 antibodies [7].…”
Section: Introductionmentioning
confidence: 99%
“…Вариабельность бактериального КП S. pneu moniae серотипа 3 может оказывать влияние на качество вакцинных препаратов. Для устранения этого недостатка перспективным является использование протективных синтетических олигосахаридов строго определенного химического строения, являющихся аналогами КП S. pneumoniae серотипа 3, конъюгированных с белком-носителем для индукции Т-зависимого иммунного ответа и иммунологической памяти [52][53][54][55]. Для конструирования мультивалентной пневмококковой вакцины можно использовать конъюгированные синтетические олигосахариды или их комбинацию с бактериальными КП [56].…”
Section: экспериментальные исследованияunclassified